Assessment of Bacillus species capacity to protect Nile tilapia from A. hydrophila infection and improve growth performance - Macias, Leslye; Mercado, Víctor; Olmos, Jorge (Frontiers in Cellular and Infection Microbiology, 2024)
The present study evaluated the capacity of three Bacillus species to improve health status and growth performance of Nile Tilapia fed with high levels of soybean meal and challenged with Aeromonas hydrophila. In vitro experiments showed that β-hemolysin and metalloprotease enzymes were produced by A. hydrophila throughout the exponential growth phase. In vivo experiments showed that 107 colony-forming units (CFUs)/ml of this pathogen killed 50% of control group fishes in 13 days. To evaluate the influence of Bacillus strains on health status and growth performance in Nile Tilapia, 180 fishes (33.44 + 0.05 g) were distributed in 12 tanks of 200 L each, and animals were fed twice per day until satiety. 1) Control group without Bacillus, 2) Bacillus sp1, 3) Bacillus sp2, and 4) Bacillus sp3 groups were formulated containing 106 CFU/g. After 40 days of feeding, the fishes were intraperitoneally injected with 1 ml of A. hydrophila at 2 × 107 CFU/ml, and mortality was recorded. The results showed that cumulative mortality rate was significantly (p< 0.05) lower in the Bacillus sp1 (25%), sp2 (5%), and sp3 (15%) groups, than the control group (50%). Weight gain was also significantly better (p< 0.05) in the Bacillus sp1 (36%), sp2 (67%), and sp3 (55%) groups with respect to the control group (30%). In conclusion, functional diet formulated with high levels of soybean meal and supplemented with Bacillus sp2 could be an alternative to protect Nile tilapia cultures from A. hydrophila infections and improve fish growth performance.